Flexible Non-contact Electrodes for Bioelectrical Signal Monitoring - Liu, Shuting; Liu, Xueyu; Jiang, Yanbing; Wang, Xin; Huang, Pingao; Wang, Hui; Zhu, Mingxing; Tan, Jingqian; Li, Peng; Lin, Chuang; Zhang, Guanghe; Chen, Shixiong; et al. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2018)
Physiological signals such as ECG and EMG are closely related with human health and a long term monitoring of the physiological signals would be beneficial to detect possible disorders at the early stage. The wet electrodes currently used in the clinics require adhesives gels to record high-quality signals, which might cause discomfort of the patients and introduce some risk of skin allergy. Non-contact capacitive electrodes that can be operated without skin contact have been developed in previous studies, but these electrodes were rigid with electronic components on the back, which might not be an optimal solution for long term healthcare monitoring. In this study, a flexible non-contact electrode without any electronic components on both sides was designed for the long term acquisition of bioelectrical signals to maximize subject comfort. The flexible electrode was made up of multi-layer flexible printed circuits (FPC) materials and could be bent according to the local shape to achieve better non-contact capacitive coupling with the skin. The performance of the proposed flexible electrode was compared with that of the conventional wet electrodes in different signal recording conditions. The results showed that the proposed non-contact flexible electrode can capture high quality ECG and EMG signals, and its performance was comparable to the commonly used wet electrodes. This study might provide a reliable solution with great patient comfort for the long-term monitoring of biological signals.